CSC537: Human - Computer Interaction / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics And Media (Universiti Teknologi MARA (UiTM), 2018)
This course is intended to introduce students to the concepts of human-computer interaction and apply them in designing a user interface. The components that will be covered include human and technology aspects of the HCI. These elements are important as the design and implementation of efficient, effective and user friendly computing systems depends upon understanding of those two elements. In this course, students will demonstrate their HCI knowledge via assignments that require them to analyze the user interface, designing a user interface, developing an interactive system and thus evaluating it using suitable tools and technique.